Data intensive distributed computing challenges and solutions for large-scale information management - Kosar, Tevfik 1974- (Premier reference source, 2012)
"This book focuses on the challenges of distributed systems imposed by the data intensive applications, and on the different state-of-the-art solutions proposed to overcome these challenges" - Provided by publisher